2001
DOI: 10.1038/sj.ijir.3900679
|View full text |Cite
|
Sign up to set email alerts
|

Pathophysiologic basis of erectile dysfunction. What can we learn from animal models?

Abstract: AimThis is an overview concerning nuances of the animal models that are used to study the diseases that cause erectile dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 31 publications
2
8
0
Order By: Relevance
“…Both in human and rat, decreased smooth muscle content and a corresponding decreased ratio of smooth muscle/collagen in the corpus cavernosum, are associated with age-related ED 52021. The aging process in the penis leading to defective CCSMC relaxation, which is considered the most important factor in age-related ED, causes veno-occlusive dysfunction and increases the severity of ED 22.…”
Section: Discussionmentioning
confidence: 99%
“…Both in human and rat, decreased smooth muscle content and a corresponding decreased ratio of smooth muscle/collagen in the corpus cavernosum, are associated with age-related ED 52021. The aging process in the penis leading to defective CCSMC relaxation, which is considered the most important factor in age-related ED, causes veno-occlusive dysfunction and increases the severity of ED 22.…”
Section: Discussionmentioning
confidence: 99%
“…In penile cells, hyperglycemia per se promotes activation of this pathway [29]. Conversely, NOS activity is decreased by MetS [13] and type 1 diabetes [28,29,43–49], which also increases penile fibrosis by altering the smooth muscle/fiber ratio [28,50].…”
Section: Discussionmentioning
confidence: 99%
“…Other chronic illnesses such as hypertension, alcoholism, and renal failure have also been studied and reported in animal models of ED [57]. Hypertension, alcoholism, and chronic renal failure (CRF) are closely associated with the development of ED.…”
Section: Experimental Animal Modelsmentioning
confidence: 99%
“…Studies have shown that the increase in oxidative stress in free radical scavengers of NO such as reactive oxygen species (ROS) contributed to the mechanism of type 1 DM‐induced model [56]. The other distinct pharmacological induced animal model is the alloxan‐induced rabbit model [57]. Both drugs resulted in similar changes with alterations in the integrity of endothelial and smooth muscle cells, increased advanced glycation products and oxidative stresses, reduced NOS activity, and development of ED in animals.…”
mentioning
confidence: 99%